Use and early mortality outcomes of active surveillance in patients with intermediate‐risk prostate cancer. Issue 18 (31st May 2019) - Butler, Santino S.; Mahal, Brandon A.; Lamba, Nayan; Mossanen, Matthew; Martin, Neil E.; Mouw, Kent W.; Nguyen, Paul L.; Muralidhar, Vinayak
Abstract : Background: Certain patients with intermediate‐risk prostate cancer (PCa) may be appropriate candidates for active surveillance (AS). In the current study, the authors sought to characterize AS use and early mortality outcomes for patients with intermediate‐risk PCa in the United States. Methods: The novel Surveillance, Epidemiology, and End Results Active Surveillance/Watchful Waiting database identified 52, 940 men diagnosed with National Comprehensive Cancer Network intermediate‐risk PCa (cT2b‐c, Gleason score of 7, or a prostate‐specific antigen level of 10‐20 ng/mL) and actively managed (AS, radiotherapy, or radical prostatectomy) from 2010 through 2015. The Cuzick test assessed AS time trends, and logistic multivariable regression characterized features associated with AS. Fine‐Gray and Cox modeling determined PCa‐specific mortality (PCSM) and overall survival, respectively. Results: The rate of AS increased from 3.7% in 2010 to 7.3% in 2015, and from 7.2% to 11.7% among men aged ≥70 years. Among men with favorable and unfavorable intermediate‐risk disease, the use of AS increased from 7.2% to 14.9% and from 2.2% to 3.8%, respectively (all P value for trend, <.001). The mean age of those patients managed with AS decreased from 69.9 years to 67.9 years ( P  = .0004). Factors found to be associated with AS included favorable risk disease; black race; higher socioeconomic status; older age; and diagnosis in the West, Northwest, or Midwest regions of the United States. The 5‐year PCSM rate was comparable to AS versus treatment among patients with low‐risk and favorable intermediate‐risk disease, but was worse with AS among those with unfavorable intermediate‐risk disease (PCSM, 1.3% vs 0.5%; adjusted hazard ratio, 2.48 [95% CI, 1.11‐5.50; P  = .026]) and intermediate‐risk disease overall (PCSM, 1.1% vs 0.4%; adjusted hazard ratio, 2.34 [95% CI, 1.25‐4.37; P  = .008]). Conclusions: The use of AS for patients with intermediate‐risk PCa is increasing across the United States, particularly for older men and those with favorable intermediate‐risk disease. Early estimates of cancer‐specific and overall mortality rates are low with AS, although significantly higher compared with treatment. Abstract : The use of active surveillance (AS) for patients diagnosed with intermediate‐risk prostate cancer is rising across the United States, particularly among older men and those with favorable intermediate‐risk disease. Early estimates of cancer‐specific and overall mortality rates are low with AS, although significantly higher compared with treatment.